Math, asked by bhaveshvk18, 1 year ago

hey

 \sqrt{x}  + y = 7 \\ x +  \sqrt{y}  = 11
find the values of x and y​

Answers

Answered by sparkle0072
1
x+√y=7

√x+y=11

from eq 1...

√y=7-x

y=(7-x)^2

from eq 2...

√x=11-y

substitute (7-x)^2 for y

√x=11-(7-x)^2

square both sides

x=121-22(7-x)^2+(7-x)^4

(7-x)^4=(x-7)^2*(x-7)^2=(x^2-14x+49)(x^2-14x-49)

x^4-28x^3+294x^2-1372x+2401

x=121-22x^2+308x-1078+x^4-28x^3+294x^2-1372x+2401

0=-x+121-22x^2+308x-1078+x^4-28x^3+294x^2-1372x+2401

x^4-28x^3+272x^2-1065x+1444=0

from the rational root theorem, possible roots are factors of 1444

4 is a factor of 1444 and a root of the equation...

256-1792+4352-4260+1444=0

-1536+4352-4260+1444=0

2816-4260+1444=0

-1444+1444=0

0=0

x=4
x+√y=7
4+√y=7
√y=7-4
√y=3
square both sides
y=9
x=4 and y=9

Hope it helps u..

bhaveshvk18: any other way...
Answered by LovelyG
12

Answer:

x = 9 and b = 4

Step-by-step explanation:

Given that-

 \sf  \sqrt{x}  + y = 7 \\  \sf x +  \sqrt{y}  = 11

Let us consider, √x = a and √y = b,

 \sf a + b^{2}  = 7 \:  \: ... (i)\\  \\  \sf a {}^{2}  + b = 11 \:  \:...( ii)

Multiplying equation (i) by a² and equation (ii) by a, we get -

 \sf  {a}^{2} (a +  {b}^{2} ) =  {a}^{2}  \times 7 \\  \\ \implies \sf  {a}^{3}  +  {a}^{2}  {b}^{2}  = 7 {a}^{2}  \:  \: ....( iii)

And,

 \sf a( {a}^{2}  + b) = a \times 11 \\  \\ \implies \sf  {a}^{3}  + ab = 11a \:  \:  \:....( iv)

Subtracting equation (iii) from (iv)-

\sf  {a}^{3}  +  {a}^{2}  {b}^{2}  -  ({a}^{3}   + ab) = 7 {a}^{2} - 11a  \\  \\  \implies \sf {a}^{3}  +  {a}^{2}  {b}^{2}  -  {a}^{3}  -  ab= 7 {a}^{2} - 11a \\  \\ \implies \sf {a}^{2}  {b}^{2} - ab = 7 {a}^{2} - 11a \\  \\ \implies \sf ab(ab - 1) = a(7a - 11) \\  \\ \implies \sf b(ab - 1) = 7a - 11 \\  \\ \implies \sf ab {}^{2}  - b = 7a - 11 \\  \\ \implies \sf  - b = 7a - ab {}^{2}  - 11 \\  \\ \implies \sf  - b = a(7 - b {}^{2} ) - 11 \\  \\ \implies \sf a(7 -  {b}^{2} ) = 11 - b \\  \\ \implies \sf a =  \frac{11 - b}{7 -  {b}^{2} }

By using hit and trial method, we will find the value of b.

Let b = 1,2...

When b = 2,

\implies \sf a =  \frac{11 - b}{7 -  {b}^{2} }  \\  \\ \implies \sf a =  \frac{11 - 2}{7 - 2 {}^{2} }  \\  \\ \implies \sf a =  \frac{9}{3}  \\  \\ \implies \sf a = 3

Now, find x and y:

\implies \sf  \sqrt{x}  = a \\  \\ \implies \sf  \sqrt{x}  = 3 \\  \\ \bf squaring \: both \: sides :  \\  \\ \boxed{ \therefore \:  \bf x = 9} \\  \\ \implies \sf  \sqrt{y}  = b \\  \\ \implies \sf  \sqrt{y}  = 2 \\  \\ \bf squaring \: both \: sides :  \\  \\ \boxed{ \therefore \:  \bf y= 4}

Hence, the value of x is 9 and y is 4.


bhaveshvk18: NYC one... thank u
LovelyG: Welcome :)
Similar questions